2020
DOI: 10.1101/2020.03.21.20037267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of SARS-CoV-2 infection upon male gonadal function: A single center-based study

Abstract: medRxiv preprint Funding Information: Health Commission of Hubei Province scientific research project (No. WJ2019Q048 to M.Z.) Conflict of interest:We declare no conflict of interest. Abstract:Since SARS-CoV-2 infection was first identified in December 2019, it spread rapidly and a global pandemic of COVID-19 has occurred. ACE2, the receptor for entry into the target cells by SARS-CoV-2, was found to abundantly express in testes, including spermatogonia, Leydig and Sertoli cells. However, there is no clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
256
3
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(293 citation statements)
references
References 21 publications
15
256
3
13
Order By: Relevance
“…Additionally, stromal cells in reproductive system (ovary and testis) and thyroid gland were also identified as potential target cells under the condition of viremia, suggesting potential injuries in these tissues. Actually, a recent study reported a significant change in certain male sex hormones in COVID-19 male patients [46], which is consistent with the notion that testis is potentially targeted by SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, stromal cells in reproductive system (ovary and testis) and thyroid gland were also identified as potential target cells under the condition of viremia, suggesting potential injuries in these tissues. Actually, a recent study reported a significant change in certain male sex hormones in COVID-19 male patients [46], which is consistent with the notion that testis is potentially targeted by SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 80%
“…SARS is known to cause orchitis and destruction to male germ cells 38 . Similar effect from COVID-19 was speculated, but a most recent study had just provided the first direct evidence that SARS-CoV-2 infection impacts male sex hormones 39 . Similarly, small intestine is the tissue with the second highest level of ACE2 expression, while SARS-CoV-2 was found in stool samples of COVID-19 patients both in China and the United States 7,42 , even after the viral RNA decreased to undetectable level in respiratory tract 43 .…”
Section: Discussionmentioning
confidence: 57%
“…As one of the drug candidates against the epidemic, GS-5734 mainly exerts antiviral therapeutic effects against the COVID-19 virus. It has been reported that the COVID-19 virus has damaging effects on the male reproductive system and kidneys, such as orchitis and causing sterility (15,16). The balance between the treatment of reproductive damage caused by viruses and the reproductive toxicity caused by the drug may be an interesting research content.…”
Section: Discussionmentioning
confidence: 99%